Flower-like MnNi2O4-MnNi2S4 core@shell composite electrode as battery-type supercapacitors. (30th November 2022) - Lv, Xinrong; Chen, Lu; Min, Xiaoqin; Lin, Xiaoyun; Ni, Yongnian
Abstract: A novel flower-like MnNi2 O4 -MnNi2 S4 core@shell composite electrode was synthesized by a simple hydrothermal in - situ growth reaction and used as battery-type supercapacitors. MnNi2 S4 nanosheets as "shell" were observed to be evenly grown onto the surface of MnNi2 O4 nanoflower as "core" to form a typical core@shell structure. Such structures greatly increase the abundant electrochemically active sites of materials. In addition, the X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscope (TEM) test results showed that MnNi2 S4 is an amorphous structure, which can provide more channels for electron transmission and ion diffusion. Consequently, the MnNi2 O4 -MnNi2 S4 electrode shows outstanding electrochemical performance. When a current density is 1 A g −1, the specific capacity for the MnNi2 O4 -MnNi2 S4 reaches up to 1302.0C g −1, which is 2.7 times higher than that of the MnNi2 O4 . Furthermore, the MnNi2 O4 -MnNi2 S4 shows preeminent cycling performance, and its specific capacity retention rate can still be maintained at 96.67 % after 5000 cycles at 20 A g −1 . Additionally, when the power density is 774.95 W kg −1, the energy density for the MnNi2 O4 -MnNi2 S4 is up to be 57.26 Wh kg −1 . Therefore, the device-MnNi2 O4 -MnNi2 S4 //AC shows good practical application prospect. Highlights: A novel MnNi2 O4 -MnNi2 S4 nanoflower@nanosheet was firstly synthesized. The MnNi2 O4 -MnNi2 S4 electrode material shows excellent electrochemical performance. The MnNi2 O4 -MnNi2 S4 //AC shows excellent self-discharge characteristics and a low leakage current.